Desain Aplikasi Layanan Kesehatan Home Care Menggunakan Metode User Centred Design (UCD) - Setiawan, Agustinus Eko; Zulkifli, Zulkifli; Andika, Tahta Herdian; Aras, Irsan; Pasaribu, Alfredo (Institut Teknologi Garut, 2024)
In today's digital era, using applications to support the health service process is very useful. The service that everyone expects is one that truly serves and makes it very easy. In this research the author proposes to develop a Home Care application which aims to facilitate public access to health services. People do not need to go to health centers or hospitals, but medical personnel will visit patients. The Home Care Health Service which is presented via the web platform is designed with a UCD (User Centered Design) approach to overcome the challenges faced by users in using the Home Care application provided. Users can easily understand the functions of these application modules in just one use. The User Centered Design (UCD) method succeeded in obtaining usability testing results with an average percentage of 83.72%. Thus, the Home Care application has succeeded in creating a system that is user-friendly and very useful.